PEMILIHAN KEPALA DAERAH PASCA REFORMASI 1998 DI INDONESIA DALAM MEWUJUDKAN DEMOKRASI LOKAL - Alviani Salim (FH HTN 16 UMY 059, 2016)
Local election is one of the importants of democracy in Indonesia. After the 1998 political reform Indonesia has tried to find out some model of local election. The research aims to evaluate the implementation of local democracy in the election of the Head of Regions (Governor, Regents, Mayors) after the 1998 political reform in Indonesia. The research is a normative legal research with statute approach. The data used is secondary data. The data is taken through library research which consists of primary legal source, secondary legal source and tertiary legal source. The result of research shows that there are 4 models of Local Election of the Head of Regions after the 1998 political reform, they are as follows: 1) Indirect Local Election, 2) Direct Election. Direct election has some various models such as direct local election without independent candidate, direct election with independent candidate and direct election with simultaneous election. The practice of simultaneous local election also shows some negative impacts such as more social conflict, lack of security staffs to secure the elections, more disputes brought to the Constitutional Court. The research recommends that the DPR and Government have to evaluate further the model of simultaneous local election in a better schedule such as conducting local election based on particular zones. Keywords: models of local election, local democracy, head of regions